Rosat observations of hyperluminous IRAS galaxies: Upper limits and their implications - Wilman, R (1999)
We discuss the implications, for the properties of hidden active nuclei and starbursts, of the non-detection of four hyperluminous IRAS galaxies with long, pointed ROSAT HRI observations.The results of a search of the ROSAT archive for serendipitous observations of ULIRGs in the catalogue of Clements et al. (1996,1998) are also presented. The detection of a new source is announced.